Achieving synergy between strategy and innovation: The key to value creation - C. Brooke Dobni (International Journal of Business Science & Applied Management (IJBSAM), 2010)
An innovation perspective provides an unencumbered clean sheet view of the future, as it is only concerned with what opportunities lie ahead. It prompts the organization to consider the question of "what future state do we want to achieve?" as opposed to the orchestrated approaches of strategic planning that promotes incrementalism. The perspective chosen will often determine whether an organization is a competitive innovator and competitive imitator. In today's economic environment, organizations are required to create differentiable value. To do so requires a certain synergy between strategy and innovation. This article outlines the importance of innovation, but more importantly discusses the relationship between strategy and innovation. It argues that strategic innovation is logical, yet strategy and innovation are quite different, both in terms of definition and function. These differences are identified, and approaches to achieving synergy are outlined.
Keywords: 650; innovation; competitive advantage; opportunity space; strategic innovation